Pendampingan Siswa SMK Dalam Mengelola Intensitas Penggunaan Gadget Untuk Mendukung Pembentukan Karakter Positif - Suwandi; Pitaloka, Dinda Widiya; Ismadini; Alisia, Selvi; Wijaya, Sabar Bagus (CV. Kurnia Grup, 2026)
This community service initiative was motivated by the high frequency of gadget use among vocational high school students, which has led to a decline in study discipline, self-control, academic responsibility, and digital ethics. This issue is not only related to technology but also concerns the character development of students in the digital age. The focus of this service activity is to guide students in managing their gadget use through a digital self-management approach at SMK Sasmita Jaya 2 Pamulang. The objectives of this activity are to enhance students’ understanding of healthy gadget use, foster more productive gadget usage habits, and strengthen students’ discipline and sense of responsibility. The methods used include participatory and educational approaches, as well as guidance through four stages: initial assessment, digital literacy education, digital self-management practice, and monitoring and reflection on behavioral changes. Data was collected through observation, simple questionnaires, reflection journals, and group discussions, and was then analyzed using qualitative descriptive methods. The results of the program indicate positive initial behavioral changes, marked by increased student awareness regarding the need to limit gadget use, reduced use for non-academic activities, improved focus on learning, and a growing sense of responsibility in completing assignments. Additionally, students began to demonstrate better digital communication etiquette and initial ability to manage technological distractions. Thus, this PKM activity is effective in building a foundation of positive digital character among vocational high school students through systematic and sustained mentoring.